Proverbs in the representation of the linguistic picture of the world: theoretical analysis of the problem - Farida, Orazakynkyzy; Aliya, Anipina; Raikhan, Ozgambayeva; Yktiyar, Paltore; Kuralay, Permakhan (International Journal of Psychosocial Rehabilitation, 2020)
At present, in the context of anthropocentric research, the study of various aspects of human life - the image of the national mentality, which has a special content in terms of its function, physical and spiritual significance, language and culture, is very relevant. Many scientific works have been written on the inseparable link between thought, culture and language. Scientists have studied the ability of language to depict the world around a person - the realities of his life, with many everyday details, as well as the social self-knowledge of the people and their culture, customs and traditions, mentality and national character, value system, etc. noted that it is dense.By looking at language units from a linguocultural point of view, it is possible to see that the language has some very important verbal meanings that reflect the cultural and historical experience of the people and the peculiarities of their worldview, reflecting the linguistic mentality of a particular ethnic group.